Mezőgazdasági munkavégzés és munkakörülmények a sajtó tükrében - Móré, Mariann (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
In the last fifty years there were three major changes in the life of the Hungarian province, that has meant a significant challenge and required extraordinary adaptibility. Within one generation, working conditions, social relationship and social values of the provincial population have completely changed. Many social studies deal with presenting these transformations. The non-expert newspaper readers, however, get informed from the mass media, and not from the white papers of the sociologists; so, they evaluate the agricultural potential, situation and development based on these inputs. In my current study, I am looking for the answer on what kind of tendentious concerted occurence do readers use to form their opinion about the working conditions and the jobs of the farmers. Of course, besides my study, a conclusion about the agriculture can also be made based on other areas of mass media. My aim with the current study was to outline a trend using 700 articles about agriculture.